High-dose liraglutide improves metabolic syndrome in poor responders to bariatric surgery - Vinciguerra, Federica; Piazza, Luigi; Di Stefano, Carla; Degano, Claudia; Pulvirenti, Alfredo; Baratta, Roberto; Frittitta, Lucia (Frontiers in Nutrition, 2023)
Background. Bariatric surgery (BS) represents the most effective therapy for obesity class III, or class II with at least one weight-related comorbidity. However, some patients have insufficient weight loss or clinically relevant weight regain after a successful primary procedure. This study aimed to assess the efficacy of liraglutide treatment on weight loss, body composition and improvement of metabolic syndrome (MS) in patients defined as poor responders after BS.Methods. The study involved 59 non-diabetic adults with obesity (M/F: 17/42, age: 38.6 ± 11.8 years, BMI 38.3± 5.5 kg/m2) who had been treated with BS and experienced a poor response, categorized as either IWL (insufficient weight loss) or WR (weight regain). All patients were prescribed pharmacological therapy with liraglutide and attended nutritional counselling. Anthropometric and clinical measurements, body composition and the presence of MS defined according to the ATP-III classification were evaluated before starting liraglutide and after 24 weeks of treatment.Results. After 24 weeks of treatment with liraglutide, the mean weight loss was 8.4±3.6% with no difference between gender, bariatric procedure, or type of poor response (IWL or WR). A significant decrease in fat mass, free-fat mass and total body water was documented. After 24 weeks, patients presented significantly lowered fasting glucose, total cholesterol, triglycerides, AST and ALT. The prevalence of MS was reduced from 35% at baseline to 1.6% after 24 weeks. No patients discontinued the treatment during the study.In patients who experience poor response after BS, liraglutide is well tolerated and promotes significant weight loss, ameliorates cardiometabolic comorbidities, and reduces the prevalence of MS.